Identification of C3d receptors on Candida albicans. - Calderone, R A (1988)
Pseudohyphal but not yeast forms of Candida albicans possess both iC3b and C3d receptors, as determined by rosetting with erythrocytes carrying iC3b (EAC3bi) or C3d (EAC3d). Rosetting with EAC3d was markedly reduced when pseudohyphae were heat killed or treated with trypsin or pronase but was not inhibited by several saccharides or aminosaccharides, including alpha-methyl-D-mannoside, or by pretreatment of pseudohyphae with concanavalin A. However, mannoproteins obtained by concanavalin A affinity chromatography of whole pseudohyphal extracts inhibited the attachment of EAC3d to C. albicans, whereas soluble (nonmannosylated) proteins were less active. Thus, although the C3d receptors appeared to be glycosylated, the oligosaccharide component of the receptor was apparently not involved in the recognition of C3d. To isolate these receptors, whole-cell extracts were separated by DEAE-Trisacryl chromatography. Fractions that inhibited rosetting were pooled and affinity purified by C3d-Thiol-Sepharose chromatography. The eluate from this affinity column inhibited attachment of C. albicans to EAC3d. Monoclonal antibodies to C. albicans were prepared, and three of these antibodies blocked rosetting. Western blotting (immunoblotting) with these antibodies indicated the presence of 62- and 70-kilodalton receptors for C3d in the extracts purified by C3d affinity chromatography and separated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis.